COMMUNITY INTERVENTIONS IN MARGINALIZED RURAL AREAS FROM THE APUSENI MOUNTAINS - ROMNANIA (PANGEEA, 2025)
This study presents some of the most pressing contemporary social problems faced by members of rural communities in the Apuseni Mountains. The early identification of socio-economic problems in disadvantaged areas can contribute to solving these problems and to the social reinsertion of vulnerable groups. The study highlights the socio-economic problems faced by rural communities in the Apuseni Mountains and identifies appropriate community practices for diminishing the negative effects on the population in these marginalized areas. The first part presents the main characteristics of the mountain areas in the Moti country and the socio-economic problems faced by the members of these communities. In conclusion, the paper proposes community intervention practices involving both those interested in solving their own problems as well as local authorities and non-governmental institutions operating in this area. The investigation uses data from the 2011 Census and on-site field research, conducted in two communes (Bistra and Avram Iancu), including interviews with local officials and group discussions to identify problems and to develop interventions. Proposals for community social interventions emphasize improving living conditions, ensuring equal opportunities for at-risk children and their families, promoting intercultural activities, and developing local development plans through bottom-up and top-down collaboration. The study stresses the importance of collaboration among institutions and communities to improve the quality of life of vulnerable people and groups.
Keywords: marginalized areas; disadvantaged communities; vulnerable groups; community interventions; social re-insertion; public-private partnership